#Girlswithtattoos: o corpo como território social - Almeida, Amanda Queiroz de (2017)
When we come across tattooed bodies, we can fall into a semiotic questioning of the meaning of each drawing engraved on the individual's skin. What we do not think is that perhaps that or those tattoos mean more than the simple symbolism of drawing; Means that the person who is tattooed tries to get their space, their social territory, and their individuality in a society where "being different" has become normal. This is your performance to the world. The body is appropriate for enunciation and visibility, evading normativity, it becomes a producer of affects, an articulating element in a field of discursive, subjective and political practices. And what’s like when women are tattooed? Another very current discussion of postmodern society is gender equality. Little by little, girls and women have been uniting and conquering their spaces and places of speech, when talking about gender equality, feminism, violence against women, oppression, and many other issues that are part of the daily life of women in a model society traditionally patriarchal and sexist. The goal of this research is to understand the use of the hashtag #girlswithtattoos on Instagram: how and why women enunciate themselves, how people receive this enunciation, and what is their importance in the fight for gender equality. Through a collection of Instagram images from the Main Publications category of a hashtag with more than 10 million publications, the research unites the study of body and gender to show how this hashtag represents enunciation and empowerment, since many women around the world use it to post photos of their tattooed bodies, showing that there is no aesthetic pattern, beauty pattern, body pattern. All are beautiful, powerful, tattooed, and therefore contemplated to be like this: free.